PEMANFAATAN CANGKANG KERANG SIMPING (Amusium pleuronectes) SEBAGAI SUMBER KALSIUM PADA PRODUK EKSTRUDAT - Tri Winarni Agustini; Susanna Endah Ratnawati; Bambang Argo Wibowo; Johannes Hutabarat (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Asian moon scallop shell can be used as alternative calcium source, and its processing into calcium flour can be used to decrease waste of fresh scallop processing. Asian moon scallop is one of potential commodity alongside east coastal of Central Java. The application of calcium flour in food need to be done as calcium suplement for middle class society. The absorbption of calcium in the body is depending of some factors, one of them is calcium and phosphorus ratio in the food. The aims of study was to examine the effect of addition calcium flour, millet flour and corn flour in extrudate with consideration on ratio of calcium and phosphorus. The parameter analyzed were proximate test, calcium and phosphorus test and physical test (hedonic scale and breaking strength). This research used experimental laboratories and descriptive with Completely Randomised Design (CRD). Data were analyzed by Analysis of Varians (ANOVA) and Honestly Significant Difference (HSD). Hedonic value was tested by Kruskall Wallis analysis. Result show that extrudate snacks gave calcium and phosphorus ratio approaching 3 : 1 (Ca:P). Calcium content in extrudate with modification of calcium flour and corn flour is 582.66 mg/ 100 g and phosphorus content is 180 mg/100 g. Whereas extrudate with modification of calcium flour with millet flour is 950 mg/ 100 and phosphorus content is 280 mg/ 100 g. Breaking strength values in extrudate with modification calcium flour and corn flour are 8.81 kg.F and 5.32 kg.F in modification with calcium flour and millet flour. Values of hedonic test are 6.89 ≤ µ ≤ 7.57 in extrudate modification calcium flour and corn flour and 7.07≤ µ ≤ 7.77 in extrudate modification calcium flour and millet flour. This product has market potential and can be used as calcium source in the society.Key words : calcium flour, Asian moon scallop, formulation and extrudate.